Assessing the development status of intraoperative fluorescence imaging for anatomy visualisation, using the IDEAL framework. Issue 1 (4th November 2022) - Ishizawa, Takeaki; McCulloch, Peter; Stassen, Laurents; van den Bos, Jacqueline; Regimbeau, Jean-Marc; Dembinski, Jeanne; Schneider-Koriath, Sylke; Boni, Luigi; Aoki, Takeshi; Nishino, Hiroto; Hasegawa, Kiyoshi; Sekine, Yasuo; et al.
Abstract : Objectives: Intraoperative fluorescence imaging is currently used in a variety of surgical fields for four main purposes: visualising anatomy, assessing tissue perfusion, identifying/localising cancer and mapping lymphatic systems. To establish evidence-based guidance for research and practice, understanding the state of research on fluorescence imaging in different surgical fields is needed. We evaluated the evidence on fluorescence imaging used to visualise anatomical structures using the IDEAL framework, a framework designed to describe the stages of innovation in surgery and other interventional procedures. Design: IDEAL staging based on a thorough literature review. Setting: All publications on intraoperative fluorescence imaging for visualising anatomical structures reported in PubMed through 2020 were identified for five surgical procedures: cholangiography, hepatic segmentation, lung segmentation, ureterography and parathyroid identification. Main outcome measures: The IDEAL stage of research evidence was determined for each of the five procedures using a previously described approach. Results: 225 articles (8427 cases) were selected for analysis. Current status of research evidence on fluorescence imaging was rated IDEAL stage 2a for ureterography and lung segmentation, IDEAL 2b for hepatic segmentation and IDEAL stage 3 for cholangiography and parathyroid identification. Enhanced tissue identification rates using fluorescence imaging relative to conventional white-light imaging have been documented for all five procedures by comparative studies including randomised controlled trials for cholangiography and parathyroid identification. Advantages of anatomy visualisation with fluorescence imaging for improving short-term and long-term postoperative outcomes also were demonstrated, especially for hepatobiliary surgery and (para)thyroidectomy. No adverse reactions associated with fluorescent agents were reported. Conclusions: Intraoperative fluorescence imaging can be used safely to enhance the identification of anatomical structures, which may lead to improved postoperative outcomes. Overviewing current research knowledge using the IDEAL framework aids in designing further studies to develop fluorescence imaging techniques into an essential intraoperative navigation tool in each surgical field.